Ocena atrakcyjności inwestycji w akcje spółek społecznie odpowiedzialnych na podstawie indeksu RECPECT - Gołaszewska-Kaczan, Urszula; Kilon, Jarosław; Marcinkiewicz, Jacek (Annales. Etyka w Życiu Gospodarczym, 2016)
In both theory and practice, it is emphasised that engaging in CSR actions brings many benefits to companies. One of the commonly listed advantages is more trust from investors, which enables the achievement of superior returns from securities issued by socially responsible firms. The paper endeavours to investigate whether this benefit can be also noticed among businesses in the Polish index of socially responsible companies RESPECT. The study involves firms included in the RESPECT index from its inception (November 2011) to the end of 2015. The authors compared the RESPECT index with selected Polish market indices between 2009 and 2015. Empirical studies, based on an analysis of returns, risk, dividend yields and shareholder structure, facilitated the assessment of the attractiveness of investments in the shares of socially responsible businesses against the background of other firms quoted on the Warsaw Stock Exchange.